The Technology-Based Learning Models: Building 21st Century Skills in Early Childhood - Dinda Permatasari; Niki Agung Wahyuni; Adi Fitra Andikos (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Education in Indonesia is faced with various extraordinary challenges as the era of science and technology continues to develop rapidly. This development will have a significant impact and continue to increase competitiveness between individuals with life challenges, especially in the world of education. Educational institutions, especially teachers as educators, have a very effective task in providing learning in order to guide children to be able to educate the future of the nation so that they can face the challenges of contemporary developments. As in the 21st Century, this is a century where technology is developing very rapidly. After running for 20 years, technology has become part of our daily lives. In this century, social media terms such as WhatsApp, Facebook, Twitter, Instagram and many others have begun to be known. As technology develops, it also has an impact on the learning system. Especially for educators and especially students who experience the emergence of various technologies that can be used in the learning process. Therefore, the term 21st century learninge merged. Where in the 21st century, skills in using technology in the process, especially learning, are very necessary, especially for educators, starting from educators in kindergartens or play groups or what we usually call early childhood.